Effects of menopause, gender and age on lipids and high-density lipoprotein cholesterol subfractions. Issue 1 (May 2015) - Anagnostis, Panagiotis; Stevenson, John C.; Crook, David; Johnston, Desmond G.; Godsland, Ian F.
Highlights 1833 men and pre- and postmenopausal women were studied. Menopause and postmenopausal aging adversely affected lipid risk factors. Triglycerides and non-HDL cholesterol were particularly affected by menopause. Male gender had generally greater adverse impact than postmenopausal status.